Bladder involvement in placenta accreta spectrum disorder with placenta previa: MRI findings and outcomes correlation. Issue 160 (March 2023) - Jariyawattanarat, Watchaya; Thiravit, Shanigarn; Suvannarerg, Voraparee; Srisajjakul, Sitthipong; Sutchritpongsa, Pavit
Highlights: Accurate preoperative diagnosis of PAS with bladder involvement is important. MRI is useful in predicting bladder involvement in invasive placentation by using the combination of loss of the chemical shift artifact in the SSFE sequence and abnormal vascularization at the uterovesical interface, yielded up to 100% specificity. PAS with bladder involvement correlated with massive surgical blood loss. Abstract: Background: Placental accreta spectrum (PAS) disorder with bladder involvement can be associated with maternal and neonatal morbidity. Magnetic resonance imaging (MRI) may provide accurate preoperative diagnoses. Objective: This study had 2 aims: to retrospectively review the MRI findings for bladder involvement in PAS with placental previa and to correlate bladder involvement with maternal and neonatal outcomes. Materials and methods: MRI images of 48 patients with severe PAS (increta and percreta) with placenta previa/low-lying placenta were evaluated by 2 experienced radiologists blinded to the final diagnoses. Nine MRI findings and stepwise logistic regression analysis were assessed to identify predictive MRI findings for bladder involvement. The correlations between PAS patients with bladder involvement and clinical outcomes were analyzed using Fisher's exact test. Results: Of the 48 patients, 27 did not have bladder involvement, while 21 did. Logistic regression analysis identified 2 predictive MRI features for bladder involvement. They were abnormal vascularization (OR, 6.94; 95 %CI, 1.05–45.75) and loss of the chemical shift line at the uterovesical interface (OR, 4.41; 95 %CI, 0.63–30.98). The sensitivity and specificity of the combined MRI features were 38.1 % and 100 %, respectively ( p  = 0.001). A significant correlation was found between bladder involvement and massive blood loss during surgery ( p  = 0.022). Conclusions: PAS with bladder involvement was significantly correlated with massive surgical blood loss. Prenatally, the disorder was predicted with high specificity by the combination of loss of chemical shift artifacts in the steady-state free precession sequence and abnormal vascularization at the uterovesical interface on MRI.